Preoperative prediction of curative surgery of perihilar cholangiocarcinoma by combination of endoscopic ultrasound and computed tomography. Issue 2 (1st March 2018) - Kammerer, Sara; Meister, Tobias; Wolters, Heiner; Lessing, Matthias; Hüsing, Anna; Domagk, Dirk; Floer, Martin; Wilms, Christian; Schmidt, Hartmut; Senninger, Norbert; Köhler, Gabriele; Heinzow, Hauke Sebastian
Abstract : Background: Perihilar cholangiocarcinomas are often considered incurable. Late diagnosis is common. Advanced disease therefore frequently causes questioning of curative surgical outcome. Aim: This study aimed to develop a prediction model of curative surgery in patients suffering from perihilar cholangiocarcinomas based on preoperative endosonography and computer tomography. Methods: A cohort of 81 patients (median age 67 (54–75) years, 62% male) with perihilar cholangiocarcinoma was retrospectively analyzed. Multivariate logistic regression analysis of staging variables taken from the European Staging System was performed and applied to ROC analysis. Results: The correlation of predicted rates of eligibility for surgery with actual rates reached AUC values between 0.652 and 0.758 for endosonography and computer tomography ( p < 0.05 each). Best prediction for curative surgical option was achieved by combining endosonography and computer tomography (AUC: 0.787; 95% CI 0.680–0.893, p < 0.0001). A predictive model (pSurg) was developed using multivariate analysis. Conclusions: Our predictive web‐based model pSurg with inclusion of T, N, M, B, PV, HA and V stage of the recently published European Staging System for perihilar cholangiocarcinoma results in highly significant predictability for curative surgery when combining preoperative endosonography and computer tomography, thus allowing for better patient selection in terms of possibility of curative surgery.